The Effect of Construction Banda Aceh - Sigli Toll Road on The Socio-Economic Conditions of Farmers in Aceh Besar Regency - Zikria, Virda; Iskandar, Elvira; Juliaviani, Noratun (University of Jember, 2024)
Infrastructure development, especially toll road construction, requires land availability. The infrastructure development process may affect people's daily lives. One of the infrastructures developed is the Banda Aceh-Sigli toll road. Land conversion changes the function of land from its former function to other uses so that it can have an impact on socio-economic changes in the surrounding population. The number of sub-districts in Aceh Besar Regency reaches 9 districts affected by land conversion. Of these districts, 60 samples were selected from 3 districts; Indrapuri, Cot Glie and Kuta Baro. This study examines the impact of conversion of paddy fields due to the construction of the Banda Aceh - Sigli Toll Road on the socio-economy of farmers using the Wilcoxon Signed Ranks Test. The results showed that the Banda Aceh-Sigli toll road development influenced social conditions only from environmental indicators while other indicators had no effect. As for economic conditions, toll road development affects the indicators of assets, land area, income and expenditure in the agricultural sector. While the other two indicators have no effect.